Risk analysis of hospitals using GIS and HAZUS: A case study of Yazd County, Iran. (August 2020) - Fallah-Aliabadi, Saeed; Ostadtaghizadeh, Abbas; Ardalan, Ali; Eskandari, Mohammad; Fatemi, Farin; Mirjalili, Mohammad Reza; Khazai, Bijan
Abstract: The increase in the number and severity of various disasters has put communities in danger. Hospitals and other health care facilities play an important role in managing patients and their companions. The proper functioning of the hospital's units and infrastructure networks are definitively required and disruption to any of them can threaten the patients' lives and disrupt the provision of services. Therefore, seismic hazard analysis of hospitals can help decision makers to estimate the potential losses considering available resources for related proceedings, such as upgrading the seismic resistance of existing buildings and lifelines. This study was conducted in existing hospitals in Yazd. First, the seismic risk analysis of Yazd city was conducted based on two scenarios. Second, fragility curves were prepared for each hospital building and its components including water and fuel tanks, power, and gas stations in order to determine the potential damage of different accelerations of the ground. Finally, seismic loss estimation was performed for hospitals understudy based on risk analysis maps. The results showed that the average damage to hospitals in the first and second earthquake scenarios is 42% and 23%, respectively. Among the building components, the most damages are for fuel tanks and the least for gas stations. The overall probability of damage following the first earthquake scenario is higher than the second scenario due to the proximity of the fault to the hospitals in Yazd. The results of the study can be useful in reducing earthquake risk in hospitals.